A randomized study of natalizumab dosing regimens for relapsing–remitting multiple sclerosis. (December 2021) - Trojano, Maria; Ramió-Torrentà, Lluís; Grimaldi, Luigi ME; Lubetzki, Catherine; Schippling, Sven; Evans, Karleyton C; Ren, Zheng; Muralidharan, Kumar Kandadi; Licata, Stephanie; Gafson, Arie R
Background: REFINE was an exploratory, dose- and frequency-blinded, prospective, randomized, dose-ranging study in relapsing–remitting multiple sclerosis (RRMS) patients. Objective: To examine the efficacy, safety, and tolerability of natalizumab administered via various regimens in RRMS patients. Methods: Clinically stable RRMS patients previously treated with 300 mg natalizumab intravenously for ⩾12 months were randomized to one of six natalizumab regimens over 60 weeks: 300 mg administered intravenously or subcutaneously every 4 weeks (Q4W), 300 mg intravenously or subcutaneously every 12 weeks (Q12W), or 150 mg intravenously or subcutaneously Q12W. The primary endpoint was the mean cumulative number of combined unique active magnetic resonance imaging (MRI) lesions at week 60. Results: In total, 290 patients were enrolled. All Q12W dosing arms were associated with increased clinical and MRI disease activity and closed early; ⩾39.5% of patients in each Q12W arm met rescue criteria. In the 300 mg intravenous and subcutaneous Q4 W arms, the mean cumulative number of combined unique active MRI lesions was 0.23 and 0.02, respectively; annualized relapse rates were 0.07 and 0.08, respectively; and trough natalizumab serum levels and α4-integrin saturation were comparable. Conclusion: Natalizumab 300 mg subcutaneous Q4W was comparable to 300 mg intravenous Q4W dosing with respect to efficacy, pharmacokinetics/pharmacodynamics, and safety.